Biomechanical Evaluation of the Transpedicular Nucleotomy with Intact Anulus Fibrosus. Issue 1 (April 2016) - Russo, Fabrizio; Vadalà, Gianluca; Hartman, Robert Allen; Bell, Kevin M.; Sowa, Gwendolyn A.; Vo, Nam; Kang, James D.; Denaro, Vincenzo
Introduction: Mechanical loading represents a crucial part of intervertebral disc (IVD) homeostasis. However, traditional regenerative strategies require violation of the annulus fibrosus (AF) resulting in significant alteration of joint mechanics. The transpedicular nucleotomy represents a suitable method to create a cavity into the nucleus polposus (NP), as a model to study IVD regeneration with intact AF. The aim is to study how the transpedicular tunnel (TT) and the novel mechanical nucleotomy affects the biomechanics of the NP. Material and Methods: 60 ovine lumbar FSUs (L1-L6) randomly assigned to 5 groups: Control; TT; TT + polymethylmethacrylate (PMMA), to repair the bone tunnel; Nucleotomy; Nucleotomy + PMMA. The robotic spine testing system consists of a robotic manipulator (Staubli RX90) and a six-axis load cell (JR3 Inc.). Flexion/extension, lateral bending and axial rotation were evaluated under adaptive displacement control. Axial compression was applied for 15 cycles of preconditioning followed by 1 hour of constant compression. Viscoelastic properties were determined. Results: TT has minimal effects on rotational biomechanics. The nucleotomy increases ROM and NZ displacement width while decreasing NZ stiffness. TT + PMMA has small effects in terms of ROM. Nucleotomy + PMMA brings ROM back to the control, increases NZ stiffness and decreases NZ displacement width. The nucleotomy tends to increase the rate of early creep. TT reduces early and late damping. The use of PMMA increased late elastic damping (S2) and reduced viscous damping (η2) culminating in faster resolution of creep. Conclusion: Biomechanical properties of NP are crucial for IVD repair. TT does not affect rotational stability. Mechanical changes that occur with nucleotomy are similar to those characteristics of early degeneration. These findings confirm that the NP is crucial for segmental stability in physiologic rotations.